2017
DOI: 10.1111/asj.12965
|View full text |Cite
|
Sign up to set email alerts
|

Effects of complex probiotic supplementation in growing pig diets with and without palm kernel expellers on growth performance, nutrient digestibility, blood parameters, fecal microbial shedding and noxious gas emission

Abstract: In Experiment 1, a total of 100 growing pigs (Duroc × [Landrace × Yorkshire]) with an average initial body weight (BW) of 24.88 ± 1.57 kg were randomly allotted to 2 × 2 factorial arrangement with two concentrations of palm kernel expellers (PKE) in diets at 0% or 10%, and two concentrations of supplemental probiotics at 0 or 6.0 × 10 colony-forming units/kg. There were five replicate pens per treatment with five pigs per pen. In Experiment 2, eight barrows with average initial BW of 25.78 ± 0.19 kg were allot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
(47 reference statements)
2
16
0
1
Order By: Relevance
“…Therefore, they suggested that yeast supplementation during the postweaning period might have happened too late to affect growth performance. The observed increased ATTD of DM, GE, and P with LY supplementation during the nursery phase is consistent with the findings of Shen et al (2009) and Liu et al (2018). It has been reported that LY supplementation could increase cellulolytic microbiome counts in ruminants (Newbold et al, 1995) and increase the digestion of fiber in horses and piglets (Jouany et al, 2008;Lizardo et al, 2012).…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, they suggested that yeast supplementation during the postweaning period might have happened too late to affect growth performance. The observed increased ATTD of DM, GE, and P with LY supplementation during the nursery phase is consistent with the findings of Shen et al (2009) and Liu et al (2018). It has been reported that LY supplementation could increase cellulolytic microbiome counts in ruminants (Newbold et al, 1995) and increase the digestion of fiber in horses and piglets (Jouany et al, 2008;Lizardo et al, 2012).…”
Section: Discussionsupporting
confidence: 84%
“…Bacillus and Saccharomyces cerevisiae have good largescale production performance and high stability and viability during feed preparation and storage (Ohashi and Ushida 2009), and B. subtilis, B. licheniformis, and S. cerevisiae have been listed to be added as non-toxigenic, biological supplements to livestock diets (EFSA 2013). Some studies have suggested that Bacillus or yeast could improve the growth performance (Balasubramanian et al 2016), nutrient digestibility (Liu et al 2018) and intestinal microbial balance (Lan et al 2017) in pigs. Jørgensen et al (2016) have demonstrated that the Bacillus-based probiotics significantly improved growth rate by 11.2% and F:G by 8.6% during the grower period stage (70-120 days) in pigs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the increased serum amino acids concentrations indicated that FP addition stimulated the digestion of dietary protein and the absorption of resultant amino acids, therefore improving growth performance (Wu et al, 2007). The previous studies have showed that complex probiotic, multi-enzyme preparations and herbal compounds improved the digestive and absorptive function and regulated amino acids metabolism (Kong et al, 2009;Liu et al, 2017;Omogbenigun et al, 2004;Yin et al, 2009). Additionally, increasing the circulatory aspartic acid, cysteine, arginine, proline and taurine are beneficial to immune status and anti-oxidant capacity (Wu et al, 2007⍰Zhang, Jin, Peng, Guo, & Wang, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Complex-probiotic-preparation could promote the absorption of nutrients and maintain the intestinal health by regulating the host mucosal and systemic immune function (Ren, Wang, Liu, Shen, & Yu, 2019;Valeriano, Balolong, & Kang, 2017). Probiotics has demonstrated to improve the growth performance and nutrient digestibility of livestock and poultry (Liu, Devi, Park, & Kim, 2017). Probiotics have anti-inflammatory activity and can activate dendritic cells, improve the production of cytokines, and stimulate B cells to secrete antibodies (Michele et al, 2017).…”
Section: Introductionmentioning
confidence: 99%